Ireland : Financial Sector Assessment Program-Technical Note on Macroprudential Policy Framework and Tools. (IMF Staff Country Reports; Country Report ;, 2022)
Ireland is a small open economy that is part of a monetary union and has a major financial system. Within the Euro Area (EA), Ireland comprises a relatively small proportion of aggregate GDP (3.4 percent), of which a significant portion is attributable to foreign-owned multinational enterprises (MNEs). Yet, the Irish financial system holds assets of EUR 7.9 trillion, over 18 times GDP. Since monetary policy is carried out by the European Central Bank (ECB) for the entire EA, macroprudential policy has the potential to play a critical stabilizing role for the Irish financial system.